Analisis Perilaku Pemanfaatan Pelayanan Pemeriksaan Inspeksi Visual Asam Asetat di Puskesmas Bergas pada Wanita Usia Subur di Desa Jatijajar: Behavioral Analysis of The Utilization of Examination Services Inspeksi Visual Asam Acetate at Puskesmas Bergas in Women of Childbearing Age in Jatijajar Village - Alifia Jumeisya Setiawan; Luvi Dian Afriyani (Journal of Holistics and Health Sciences (JHHS), 2023)
Puskesmas Bergas is one of the puskesmas that carries out IVA test services in Semarang Regency. The target of women of childbearing age for IVA examination in 1999 was women, 142 women who carried out IVA examination and 14 positive cases of IVA from 12 villages in the working area of Puskesmas Bergas. Karangjati Village has the highest IVA examination utilization of 16 people and Jatijajar Village has a low coverage of 1 person. Based on the interview results of Jatijajar Village Midwives and 5 women of childbearing age in Jatijajar Village, it was found that few who carried out IVA examinations were influenced by behavioral factors. Analyze the utilization behavior of IVA examination services at the Bergas Health Center for women of childbearing age in Jatijajar Village. Qualitative research methods. The population of all women of childbearing age in Jatijajar Village. The research subjects were 9 women of childbearing age in Jatijajar Village and 3 triangulation informants, namely village midwives, posyandu cadres, and IVA examination program coordinators. Instruments with structured interview guidelines. Most respondents do not know about the IVA program, for the attitude factor wus smostly support the IVA program. Ease of access to services is no obstacle but access to information is still lacking. Puskesmas are expected to carry out health promotion using media such as leaflets, etc.Village Midwives and Cadres hold promotions related to IVA examinations for women of childbearing age through various media.   ABSTRAK Puskesmas Bergas merupakan salah satu puskesmas yang melaksanakan pelayanan tes IVA di Kabupaten Semarang. Sasaran Wanita usia subur untuk pemeriksaan IVA 1999 perempuan, 142 perempuan yang melakukan pemeriksaan IVA dan 14 kasus possitif IVA dari 12 Desa wilayah kerja Puskesmas Bergas. Desa Karangjati pemanfaatan pemeriksaan IVA tertinggi 16 orang dan Desa Jatijajar cakupan rendah 1 orang. Berdasarkan hasil wawancara Bidan Desa Jatijajar dan 5 wanita usia subur Desa Jatijajar didapatkan bahwa sedikit yang melakukan pemeriksaan IVA dipengaruhi oleh faktor perilaku. Menganalisis perilaku pemanfaatan pelayanan pemeriksaan IVA di Puskesmas Bergas pada wanita usia subur di Desa Jatijajar. Metode penelitian kualitatif. Populasi seluruh wanita usia subur di Desa Jatijajar. Subjek penelitian wanita usia subur di Desa Jatijajar yang berjumlah 9 orang dan untuk informan triangulasi berjumlah 3 orang yaitu bidan desa, kader posyandu, dan koordinator program pemeriksaan IVA. Instrumen dengan pedoman wawancara tersetruktur. Sebagian besar responden belum mengetahui tentang program IVA, untuk factor sikap wus sebagian besar mendukung program IVA. kemudahan akses pelayanan tidak ada kendala namun akses informasi masih kurang. Puskesmas diharapkan melakukan promosi Kesehatan dengan menggunakan media seperti leaflet, dll.Bidan Desa dan Kader mengadakan promosi terkait pemeriksaan IVA kepada wanita usia subur melalui berbagai media.